TeV blazar observations with Whipple and VERITAS - Bradbury, S (2002)
The Whipple 10 m Imaging Atmospheric Cherenkov Telescope has laid the foundations for ground-based gamma-ray astronomy, notably by extending measurements of blazar spectra and flux variability to TeV energies and revealing a correlation between TeV gamma-ray and X-ray flares. The Very Energetic Radiation Imaging Telescope Array System, VERITAS, is a next generation Cherenkov observatory proposed to extend these measurements over the 50 GeV to 50 TeV range. The purpose of this paper is to highlight some recent results from the Whipple Observatory.